2010
DOI: 10.1021/om100352c
|View full text |Cite
|
Sign up to set email alerts
|

UV-Photoelectron Spectroscopic Studies on 2-Arylethynyl-1,3,2-benzodiazaboroles

Abstract: Gas-phase He I photoelectron spectra of a series of 2-arylethynyl-1,3,2-benzodiazaboroles BEP-X [1 (X = H), 2 (X = Me), 3 (X = OMe), 4 (X = SMe), 5 (X = NMe2), 6 (X = Br)] have been recorded and assessed by density functional theory calculations. The first ionization energies of these benzodiazaboroles are in the order 5 (7.0 eV) < 3 (7.15 eV) < 2 (7.2 eV) < 1 = 4 = 6 (7.3 eV). As an important result of this study it was disclosed that in contrast to the remaining diazaboroles the frontier orbitals of the amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…[2][3][4][5] In the course of our studies on the chemical and physico-chemical properties of 1,3,2-diazaboroles and 1,3,2-benzodiazaboroles, [6] it was demonstrated that arenes, biphenyls, thiophenes, dithiophenes and arylalkynes functionalized by 1,3,2-benzodiazaborol-2-yl units exhibit intense blue luminescence upon UV irradiation with Stokes shifts up to 9500 cm -1 and quantum efficiencies up to 0.99. [7][8][9] Our studies, however, have dis-boiling THF in the presence of lithium chloride led to the formation of the functionalized benzodiazaborole 5 as a colorless solid in 68 % yield. Compounds 1-3 and 5 were characterized by elemental analyses, IR and NMR spectroscopy ( 1 H, 11 B, 13 C) and mass spectrometry.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[2][3][4][5] In the course of our studies on the chemical and physico-chemical properties of 1,3,2-diazaboroles and 1,3,2-benzodiazaboroles, [6] it was demonstrated that arenes, biphenyls, thiophenes, dithiophenes and arylalkynes functionalized by 1,3,2-benzodiazaborol-2-yl units exhibit intense blue luminescence upon UV irradiation with Stokes shifts up to 9500 cm -1 and quantum efficiencies up to 0.99. [7][8][9] Our studies, however, have dis-boiling THF in the presence of lithium chloride led to the formation of the functionalized benzodiazaborole 5 as a colorless solid in 68 % yield. Compounds 1-3 and 5 were characterized by elemental analyses, IR and NMR spectroscopy ( 1 H, 11 B, 13 C) and mass spectrometry.…”
Section: Introductionmentioning
confidence: 89%
“…Ionization energies (IE) were calculated by using the CAM-B3LYP functional (which is particularly well suited for ionization energy evaluations; see for example ref. [9] ) with ΔSCF/ TD-DFT, which means that separate SCF calculations were performed to optimize the orbitals of the ground state and the appropriate ionic state (IE = E cation -E neutral ). The advantages of the most frequently employed ΔSCF/TD-DFT method of calculations of the first ionization energies have been demonstrated previously.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…Bond lengths and bond angles within the benzodiazaborole part of 3 are similar to those of numerous diazaboroles studied before. 17,19,22,[25][26][27] The molecule 12 may be described as a benzodiazaborole which is connected with a 2-thienylethynyl unit via the B(1)-C(11) single bond of 1.520(3) Å. Both heterocycles are linked by an essentially linear ethynyl bridge with a triple bond C(11)-C(12) bonds of 1.207(3) Å and angles B(1)-C(11)-C(12) and C(11)-C(12)-C(13) of 176.4(2)° and 178.2(3)°, respectively.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…For synthetic reasons the 1,3-diethyl-1,3,2-benzodiazaborole unit is the most frequently employed representative, and compounds containing this group as a substituent are moderately air-stable. 16,[22][23][24][25][26][27] As the BMes 2 group is known as an effective acceptor (A) and the benzodiazaborolyl unit has been suggested to be a π-donor (D) 27 the novel "push-pull"-systems [D-bridge-A] with 1,4-phenylene-, 4,4'-biphenylene-, 2,5-thiophene-and 5,5'-dithiophene-scaffolds (I-IV, Chart I) have been investigated recently. 28 Photophysical studies on these compounds reveal blue-green fluorescence and Stokes shifts for the first three representatives of 7820-9760 cm -1 in THF, whereas the Stokes shift for the last compound is significantly smaller (5510 cm -1 in THF).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of 20 with equimolar amounts of the in situ generated lithium derivatives of the appropriate arylalkynes furnished the solid compounds 34-41 in moderate to good yields [41,42]. Similarly, crystalline 2-(5 -dimesitylboryl-2 -thienylethynyl)-1,3-diethyl-1,3,2-benzodiazaborole (42) was synthesized [43].…”
Section: 32-triorgano-132-benzodiazaborolesmentioning
confidence: 99%